Kesantunan Berbahasa dalam Media Sosial : Kajian Pragmatik terhadap Komentar Online - Ila Maghfiroh; Rahmiati Rahmiati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research aims to analyze politeness strategies in online comments on social media, with a focus on the application of Brown and Levinson's politeness theory. Social media as a virtual public space presents challenges in maintaining communication ethics, especially regarding user anonymity and spontaneity. Research data is obtained from online comments on platforms such as Instagram, Twitter, and YouTube, which are relevant to certain public topics. A qualitative approach with pragmatic discourse analysis is used to identify forms of positive politeness, negative politeness and politeness violations. The research results show that positive politeness strategies are more dominant than negative politeness, especially on emotional topics. Speech act patterns that are often found include illocutionary acts in the form of support or praise, as well as perlocutionary acts that create an emotional response. Cultural factors, discussion topic, level of anonymity, and age of the user influence the application of politeness. The findings also revealed that politeness violations occurred more frequently in controversial discussions. This research provides practical implications in increasing social media users' awareness of communicating politely. In addition, digital platforms are expected to strengthen moderation features to create a healthier communication space. Further research is recommended to explore the relationship between language politeness and digital conflict in various cultural contexts.